PENGARUH KEMAMPUAN PERSONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN, PERDAGANGAN DAN KOPERASI KABUPATEN KAPUAS HULU PROVINSI KALIMANTAN BARAT - Latifah Latifah (Jurnal Khatulistiwa Informatika, 2014)
The study aims to determine how the Personal Capability And Effect Of Organizational Culture On Employee Performance Department of Industry , Trade and Cooperatives Kapuas Hulu in West Kalimantan Province . To collect the necessary , the authors use the technique of collecting data through questionnaires obtained at the Office of Industry , Trade and Cooperatives Kapuas Hulu in West Kalimantan province. Population in this study is the employees In On of Industry, Trade and Cooperatives Kapuas Hulu Province West Kalimantan as many as 51 people and taken sample using census / total sampling as many as 51 employees. Judging from the results of the analysis , it is known that the simultaneous performance ( Y ) is jointly influenced by the Personal Capability variable ( X1 ) and Cultural Organization ( X2 ). Partially, this study concluded that the Personal Capability ( X1 ) is a factor which significantly affect the performance ( Y ) variable and Cultural Organization ( X2 ) partially also a factor affecting the performance ( Y ).Keywords: Personal Ability , Organizational Culture , Performance